The dark side of crypto gaming guilds - Jirásek, Michal (Frontiers in Blockchain, 2022)
Crypto gaming guilds are an evolution of traditional gaming guilds, communities of players concentrated on mutual support. In the contrast to the scope of traditional guilds, crypto gaming guilds have been established as organizations focused on earning money. Crypto gaming guilds concentrate on players from developing countries, offering them a chance to earn income without the necessity to invest funds for playing play-to-earn games. The communication of these guilds is full of positive stories of people alleviated from poverty or raising through hierarchies of their guild. Yet this bright image has its dark side and crypto gaming guilds provide ample opportunities for criticism. While in the traditional gaming guilds players have a central role, in crypto gaming guilds they have become inferior compared to other stakeholders. The reason is that new stakeholder groups, investors and game studios, have risen to prominence as they bring in money to the guild. Given the fact that players often come from developing countries with low wages, this situation creates a potential for their exploitation. Yet even without exploitation, the content of their new jobs has characteristics very similar to infamous “bullshit jobs”, pointless and unnecessary employment. It remains open whether crypto gaming guilds will fulfill their publicly communicated promises or turn evil in the future. However, in both cases, they will face their dark side. And they will either overcome it or embrace it.